Dreams of Higher Education in the Mediterrani School Through Family Education - Garcia Yeste, Carme; Morlà Folch, Teresa; Ionescu, Vladia (Frontiers in Education, 2018)
Through Learning Communities, schools and their communities may play a key role in overcoming inequalities suffered by vulnerable populations. Learning Communities implement Successful Educational Actions (SEAs), one of which is Family Education. This action focuses on promoting basic education among community members, in addition to other adult educational and cultural activities. In this context, SALEACOM. Overcoming inequalities in schools and Learning Communities: Innovative education for a new century (2015-2017) is a Marie Curie RISE project to develop interdisciplinary solutions for and with learners most heavily affected by inequalities, including access to higher education and its quality. In this article, we focus on one experience from the Mediterrani School (Spain), where we work through SALEACOM. This school was known as a ghetto school until 2012, when they decided to transform the school into a Learning Community and to apply SEAs. This article analyses the impact of the Family Education programme in relation to families and children’s expectations of higher education and how these expectations affected children’s results. Family Education started in the Mediterrani School in the academic year 2012-2013, when the school and families conducted adult training courses. Three years later, family education had a massive response from the community, when 63 community members, 41% of the Roma enrolled in training courses. Since then, all courses are established according to the community’s decisions through their active participation. Following a communicative methodology, we conducted semi-structured interviews with a communicative orientation among some of the participants in these adult courses. The communicative analysis showed that Family Education allowed the participants, and the members of community expected continued education throughout life and access to the university. The Adult Education promoted in the Mediterrani School can have a transformative effect on educational outcomes, opening possibilities for personal and social change.